Third Molar Agenesis in Post-Medieval Chichester - Devyn Caldwell (Dental Anthropology Association, 2021)
Third molar agenesis is a dental anomaly that occurs in approximately 25% of people worldwide and results in the complete absence of one or more of the third molars in the dentition. A rise in the prevalence of congenitally absent third molars has been noted in modern populations, and it has been proposed as the final evolutionary step in the dental reduction of the human dentition. Whilst much research has been conducted in modern cohorts, relatively little has been published on third molar agenesis in archaeological assemblages. A post-medieval assemblage from Chichester was visually and radiographically analysed to determine the prevalence of this anomaly. Third molars were measured to determine if there was an association between agenesis and size reduction. Prevalence of agenesis was found to be relatively high at 42.7% and 2 of 8 measurements were found to produce significant differences. Consequently, it can be said that high rates of third molar agenesis are not solely a modern phenomenon, as many prevalence rates in recent populations are lower. However, if we are to assess the significance of size differences in third molars of those with agenesis and those without, and to detect patterns within and between these groups, assemblages with larger sample sizes are needed. In order to better understand the trajectory and evolution of this anomaly, more archaeological assemblages must be examined.